Carbapenem alternatives for treatment of bloodstream infections due to AmpC producing enterobacterales - M. Ávila-Núñez; O. Lima; A. Sousa; M. Represa; P. Rubiñán; P. Celestino; M. Garrido-Ventín; L. García-Formoso; F. Vasallo-Vidal; L. Martinez-Lamas; A. Pérez-Landeiro; M Rubianes; et al. (BMC, 2023)
Abstract Introduction Carbapenems (CR) have traditionally been the first line treatment for bacteremia caused by AmpC-producing Enterobacterales. However, CR have a high ecological impact, and carbapenem-resistant strains continue rising. Thus, other treatment alternatives like Piperacillin-Tazobactam (P-T) or Cefepime (CEF) and oral sequential therapy (OST) are being evaluated. Methods We conducted a retrospective, single-centre observational study. All adult patients with AmpC-producing Enterobacterales bacteremia were included. The primary endpoint was clinical success defined as a composite of clinical cure, 14-day survival, and no adverse events. We evaluated the evolution of patients in whom OST was performed. Results Seventy-seven patients were included, 22 patients in the CR group and 55 in the P-T/CEF group (37 patients received CEF and 18 P-T). The mean age of the patients was higher in the P-T/CEF group (71 years in CR group vs. 76 years in P-T/CEF group, p = 0.053). In the multivariate analysis, age ≥ 70 years (OR 0.08, 95% CI [0.007-0.966], p = 0.047) and a Charlson index ≥ 3 (OR 0.16, 95% CI [0.026-0.984], p = 0.048), were associated with a lower clinical success. Treatment with P-T/CEF was associated with higher clinical success (OR 7.75, 95% CI [1.273-47.223], p = 0.026). OST was performed in 47% of patients. This was related with a shorter in-hospital stay (OST 14 days [7-22] vs. non-OST 18 days [13-38], p = 0.005) without difference in recurrence (OST 3% vs. non-OST 5%, p = 0.999). Conclusions Targeted treatment with P-T/CEF and OST could be safe and effective treatments for patients with AmpC-producing Enterobacterales bacteremia.